Phosphorescent PdII–PdII Emitter‐Based Red OLEDs with an EQEmax of 20.52% - Lige Qiao; Xiangjun Kong; Kechun Li; Lequn Yuan; Yunjun Shen; Yuzhen Zhang; Liang Zhou (Advanced Science)
Abstract Three dinuclear Pd(II) complexes (1, 2, and 3) with intense red phosphorescence at room temperature are here synthesized using strong ligand field strength compounds. All three complexes are characterized by nuclear magnetic resonance, high‐resolution mass spectrometry, and elemental analyses. Complexes 2 and 3 are characterized by single‐crystal X‐ray diffraction. The crystalline data of 2 and 3 reveal complex double‐layer structures, with Pd–Pd distances of 2.8690(9) Å and 2.8584(17) Å, respectively. Furthermore, complexes 1, 2, and 3 show phosphorescence at room temperature in their solid states at the wavelengths of 678, 601, and 672 nm, respectively. In addition, they show phosphorescence at 634, 635, and 582 nm, respectively, in the 2 wt.% (PMMA) films, and phosphorescence at 670, 675, and 589 nm, respectively, in the deoxygenated CH2Cl2 solutions. Among three complexes, complex 1 shows red emission at 634 nm with phosphorescent quantum yield Ф = 67% in the 2 wt.% PMMA film. Furthermore, complex 1‐based organic light‐emitting diode is fabricated using a vapor‐phase deposition process, and their maximum external quantum efficiency reaches 20.52%, which is the highest percentage obtained by using the dinuclear Pd(II) complex triplet emitters with the CIE coordinates of (0.62, 0.38).